The Role Of Employee Resilience In Moderating The Influence Of Work Motivation And Work Discipline On Work Productivity At PT Natural Foods Sukses Makmur - Robin Robin; Ferry Hidayat; Jayastu Jayastu (Tractare: Jurnal Ekonomi-Manajemen, 2026)
The objective of this study is to determine the role of employee resilience in moderating the influence of work motivation and work discipline on employee productivity at PT Natural Foods Sukses Makmur. This study uses a descriptive quantitative method with quantitative data obtained from primary data through questionnaires and secondary data from relevant literature. The population in this study consists of all employees of PT Natural Foods Sukses Makmur, totaling 30 employees, so a saturated sampling technique is used with a total sample of 30 respondents. The results show that work motivation and work discipline have a positive effect on employee productivity, both partially and simultaneously. In addition, employee resilience is proven to strengthen the influence of work motivation on productivity, but it is not able to moderate the influence of work discipline on productivity.